Investigation of novel alkyl/benzyl (4-sulphamoylphenyl)carbamimidothioates as carbonic anhydrase inhibitors - Morteza Abdoli; Alessandro Bonardi; Claudiu T. Supuran; Raivis Žalubovskis (Taylor & Francis Group, 2023)
A library of novel alkyl/benzyl (4-sulphamoylphenyl)carbamimidothioates was synthesised by selective S-alkylation of the easily accessible 4-thioureidobenzenesulphonamide. The compounds were assayed as inhibitors of four human (h) carbonic anhydrase isoforms hCA I, II, VII, and XIII, as well as three bacterial enzymes belonging to the β-CA class, MscCA from Mammaliicoccus (Staphylococcus) sciuri and StCA1 and StCA2, from Salmonella enterica (serovar Typhimurium). Most compounds investigated here exhibited moderate to low nanomolar inhibition constants against hCA I, II, and VII. The cytosolic hCA XIII was also inhibited by these compounds, but not as effective as hCA I, II, and VII. Several compounds were very effective against MscCA and StCA1. StCA2 was less inhibited compared to MscCA and StCA1. Some compounds showed considerable selectivity for inhibiting some CA isoforms. They may thus be considered as interesting starting points for the discovery and development of novel therapeutic agents belonging to this class of enzyme inhibitors.